The end of competitive advantage how to keep your strategy moving as fast as your business - McGrath, Rita Gunther (Boston Harvard Business Review Press, 2013)
Chances are the strategies that worked well for you even a few years ago no longer deliver the results you need. Dramatic changes in business have unearthed a major gap between traditional approaches to strategy and the way the real world works now.
Includes bibliographical references.
Keywords: Strategic planning